INNOVATIONAL APPROACH TO IMMUNOTHERAPY OF FREQUENTLY AILING CHILDREN - I.N. Lupan; I.O. Samarin; A.Yu. Taturevich; A.A. Popova; A.R. Gaifulina ("Paediatrician" Publishers LLC, 2009)
This article presents results of clinical observation, carried out for the purpose of evaluation of effectiveness of immunotherapy for preventing of relapse of acute respiratory infection in group of frequently ailing children. This trial included 300 patients in age from 3 to 15 years old, which had 6 of more episodes of acute respiratory infection during last years. Synthetic dipeptide pidotimoid was prescribed to all patients with insufficient function of immune system. Patients from pidotimoid group had significantly lower pate of relapse of respiratory infections and more rapid recovery. Key words: frequently ailing children, acute respiratory infection, treatment, prophylaxis, pidotimoid. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):104-107)